Supporting Creation of New iStar Extensions through a Process - Gonçalves, Enyo; Araújo, João; Castro, Jaelson (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft); 2020: Anais Estendidos do XI Congresso Brasileiro de Software: Teoria e PráticaDO - 10.5753/cbsoft_estendido.2020.14627, 2020)
iStar is a goal-oriented requirements modelling language which has been used by industrial and academic projects of different domains. Modelling languages are commonly extended to add new constructs giving more expressiveness. iStar is often extended to incorporate new constructs. A study performed on iStar extensions identified 96 extensions and the occurrence of problems related to their quality. It was pointed out by experts in iStar extensions the need to propose a way to support the proposal of iStar extensions systematically to prevent the problem occurrence, increase the quality of extensions, and make extension creation a less challenging task. This work investigates how iStar extensions have been created and proposes a systematic way to guide the creation of quality extensions. A process to support the creation of new iStar extensions was proposed. The process was used to propose a new iStar extension and was analysed by experts. The results point to the usefulness of the process to propose new iStar extensions.